PERBANDINGAN PENGGUNAAN VERY SMALL APERTURE TERMINAL (VSAT) DAN SERAT OPTIK PADA JARINGAN ANJUNGAN TUNAI MANDIRI (ATM) DI BANDUNG - Alvin Rakhmat Wirakusumah, - (2020)
The very small aperture terminal (VSAT) network is very commonly used in Automated Teller Machines (ATMs) but at this time the fiber optic networks has also been used at ATMs as an alternative if the ATMs cannot use the VSAT network. The purpose of this study is to look at the comparison of reliability and availability of the VSAT networks between fiber optic networks that used in ATMs at Bandung City by analyzing the time of failure and repair time. The failure time was analyzed by using the NonHomogenous Poisson Process (NHPP) distribution, and the repair time was analyzed using a lognormal distribution. This study was conducted on all ATMs that used VSAT and Fiber optic networks at Bandung City in collaboration with PT. Aplikanusa Lintasarta Bandung as an internet service provider. Based on the results of calculations and analysis, the highest level of reliability is the fiber optic networks with 7,88745x10-40 % while the result of VSAT networks is 3,07483x10-76 % and fiber optic networks have the highest availability with 99,37% while the VSAT ability was 98,88%.